FTIR Investigation Of The O-H Center Dot Center Dot Center Dot Xe Interaction In Simple Carboxylic Acids In Solid Xenon - Nunes, Claudio M.; Kuş, Nihal; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Amer Inst Physics, Circulation & Fulfillment Div, 2 Huntington Quadrangle, Ste 1 N O 1, Melville, Ny 11747-4501 USA, 2012)
The O-H stretching region of the infrared spectra of a series of carboxylic acids in Xe matrices was investigated as a function of temperature. Upon increasing the temperature, the vO-H band site-components undergo reversible frequency blue-shifts, which are larger for the lowest-frequency components. This unprecedented observation indicates both that different types of O-H center dot center dot center dot Xe specific interactions occur, depending on different trapping sites, and the prevalence of stronger interactions of this type for molecules trapped in sites corresponding to lower frequency vO-H band site-components. These results are in agreement with previous investigations pointing to an increased stabilization and larger vO-H frequency red-shifts in carboxylic acid/Xe complexes bearing a specific H-bond like O-H center dot center dot center dot Xe interaction. O-H center dot center dot center dot Xe interaction energies were obtained theoretically and also estimated from the spectroscopic data. Changes in the interaction energies upon temperature variation were also evaluated. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4740243]
Keywords: Ab Initio; Matrix-isolation; Formic-Acid; Complexes; Argon; n-2; Spectra; Krypton; Energy; co; Matrix-Izolasyon; Formik Asit; Kompleksler; N-2; Spektrumlar; Kripton; Enerji